The influence of process parameters on lactic acid fermentation in laboratory scale fermenter - Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Jamal, Parveen; Mohamed Salleh, Mohamad Ramlan; Zakaria, Ruzi Aini (Asian Network for Scientific Information, 2006)
The purpose of this study was to study the influence of process parameters on the Lactic Acid Fermentation by Lactobacillus rhamnosus in laboratory scale ferrnenter. The experiment was designed by Taguchi Method using STATISTICA software. Three parameters have been chosen as the main parameters that affect significantly to the growth of L. rhamnosus; the agitation speed of the impeller, dissolve oxygen level (p02) and pH. The most influence and important parameter for the fermentation process is pH at acidic value of 6, followed by stirrer speed (rpm) and p02 even p02 supplied and rpm played similar fWlction in maintaining suitable dissolved oxygen to the cells.